Perforating scleral vessels adjacent to myopic choroidal neovascularization achieved a poor outcome after intravitreal anti-VEGF therapy - Yao, Wangjing; Xu, Jiawen; She, Xiangjun; Yu, Jiangxin; Liang, Zhi; Ye, Xin; Tao, Jiwei; Wu, Sulan; Mao, Jianbo; Chen, Yiqi; Zhang, Yun; Shen, Lijun (Frontiers in Medicine, 2022)
Background: To summarize the features of perforating scleral vessels (PSVs) in patients with myopic choroidal neovascularization (mCNV) by optical coherence tomography angiography (OCTA) and find its association with therapy response after intravitreal anti-VEGF therapy. Methods: A consecutive series of naïve patients with mCNV accepted intravitreal anti-VEGF therapy with a follow time of 12 months were enrolled. The prevalence, location and branches of PSV were judged. Projection-resoved optical coherence tomographic angiography (PR-OCTA) was used to analyze the neovascular signals between CNV and PSVs. Best corrected visual acuity (BCVA) and central macular thickness (CMT) were measured. Therapy response was assessed by the proportion of CMT changes relative to the baseline. Results: A total of 44 eyes in 42 patients with mCNV were enrolled in the study, PSV was identified in 41 eyes out of 44 eyes. Branches of PSVs were identified in 24 eyes (57.14%), 20 eyes did not have branches of PSVs (47.62%). 8 (18.18%) PSVs were adjacent to mCNV, 36(81.82%) PSVs were not adjacent to mCNV. BCVA increased (F=6.119, P < 0.001) and CMT decreased (F=7.664, P < 0.001) after anti-VEGF therapy for mCNV. mCNVs where PSVs adjacent to mCNV showed poor VA improvement and CMT changes (F=7.649, P =0.009). Conclusion: PSV adjacent to mCNV showed poor therapy response after intravitreal anti-VEGF therapy.